Intensified tropical cyclone activity in East Asia during the Maunder (solar) Minimum - Kuan-Hui Elaine Lin; Wan-Ling Tseng; Yu-Shiuan Lin; Chen-Ying Lee; Yu-Hsiang Lin; Huang-Hsiung Hsu; Pao-Kuan Wang (Proceedings of the National Academy of Sciences, 2025)
This study reports a tropical cyclone (TC) series reconstructed from documentary records that have been digitized in the REACHES database for the period of 1368–1911. The series has been validated through comparison with early instrumental data from 1884 to 1911 as well as with other reconstructions. TCs in the post-1911 period were also examined and a 653-y long (1368–2020) North Western Pacific TC chronology was studied. The peak TC frequency occurred in the 1650–1680 with a greater amplitude of variabilities in the south and east coasts of China and TC behaviors changed seasonally. The peak TC period corresponded to the Maunder Minimum which was characterized by lower land surface temperature, whereas the temperature reconstructed from marine proxies showed an anomalously warmer sea surface temperature over the western Pacific. Changing thermal contrast between land and sea likely created a more dynamic summer monsoon circulation resulting in active TC activity. This study provides important evidence and implication about the TC behavior in response to ongoing global climate change.